1992
DOI: 10.1007/bf01839186
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protein binding on ivermectin uptake by bovine brain microvessel endothelial cells

Abstract: The effect of albumin binding on ivermectin uptake and transfer across the endothelial component of the blood-brain barrier (BBB) was determined with an in vitro model comprised of bovine brain microvessel endothelial cell (BMEC) monolayers. Cellular uptake of ivermectin was limited in the absence of albumin and 90% inhibited in the presence of 10% albumin. Cell membrane association of ivermectin, as followed by fluorescent probe labelling, was observed only at high (micromolar) concentrations of the drug. Mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The plasma binding of ivermectin and other related macrocyclic lactones is mainly due to association with high-density lipoproteins (HDL) (Bassissi et al, 2004) whereas binding to albumin is of minor importance (Audus et al, 1992). In various animal species (cattle, sheep, goat, rabbit, pig) no difference in the binding pattern of MLs to lipoproteins was reported (Bassissi et al, 2004), consequently this is unlikely to be the cause of the breed differences in pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma binding of ivermectin and other related macrocyclic lactones is mainly due to association with high-density lipoproteins (HDL) (Bassissi et al, 2004) whereas binding to albumin is of minor importance (Audus et al, 1992). In various animal species (cattle, sheep, goat, rabbit, pig) no difference in the binding pattern of MLs to lipoproteins was reported (Bassissi et al, 2004), consequently this is unlikely to be the cause of the breed differences in pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Our results compare favorably, in a qualitative manner, with the studies of Wang et al (14) who showed about a 3-fold enhancement of rhodamine 123 uptake Rose Despite being relatively lipophilic, ivermectin typically achieves its lowest concentrations in the brain (11). Supporting that observation was our previous work which demonstrated that the uptake of ivermectin by bovine BMECs was a limited process and subject to further restrictions in the presence of serum (7). Until recently, however, an exception existed in that certain rough-coated collies, exhibit higher brain concentrations of ivermectin compared with "normal" rough-coated collies (23).…”
Section: Discussionmentioning
confidence: 77%
“…Previously our laboratory investigated the uptake of ivermectin by bovine brain microvessel endothelial cells (BMECs) (7) and canine BMECs from ivermectin sensitive and ivermectin tolerant rough-coated collies (8). Ivermectin is a complex macrocyclic lactone which possesses a broad spectrum of activity against several species of nematodes, arachnids, and insects that act as parasites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Second, 93% of ivermectin is bound to plasma proteins that limit its cellular uptake by endothelial cells. 6 Considering both the total plasma concentration and protein binding, the free plasma concentration of ivermectin would be 250 times lower than the concentration required to reduce viral replication of SARS-CoV-2 in vitro (Figure 1). Third, whilst there is no data on the tissue penetration of ivermectin in human lungs, the total concentration of ivermectin in calves injected with 200 μg/kg reached only 100 ng/g (approx.…”
mentioning
confidence: 99%